Analisis Perbandingan Perhitungan dan Pelaporan PPh Pasal 21 Terutang WP Suami Istri: NPWP Gabungan dan Memilih Terpisah - DESY CHRISNA SETYANINGRUM (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2026)
The modernization of the tax administration system through Coretax has changed taxpayers’ understanding of tax obligations within the family context. In accordance with the Income Tax Law, families in Indonesia essentially adhere to the principle of the economic unit. However, in practice, married couples may choose to combine their Taxpayer Identification Numbers or fulfill their tax obligations separately. This choice will impact both tax calculation and reporting. The subjects of this Final Project Report involve Mr. X and Mrs. X, both of whom have different occupational backgrounds: Mr. X receives income from a single employer, while Mrs. X is self-employed. From a calculation perspective, whether under a combined or separate Taxpayer Identification Number, the total tax liability for both tax statuses is the same. The difference lies in who bears the responsibility for any shortfall in the tax liability. The difference is more pronounced in the reporting procedures, where combining provides simpler administrative convenience because it only needs to be reported in the husband’s single Annual Tax Return. Meanwhile, choosing to keep separate Taxpayer Identification Numbers requires a more complex reporting process, as both spouses are required to file their own annual tax returns. Therefore, combining Taxpayer Identification Numbers is a step that should be prioritized by couples who want to simplify their tax administration.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: PERHITUNGAN PELAPORAN